Essays on collective coping in Sri Lanka - Perera, Ashira Elanee (2017)
The aim of the thesis is to contribute to our understanding of how individuals in developing countries cope when faced with environmental risks. These themes are explored while focusing on small-scale farming communities in Wellawaya, south-east Sri Lanka, that are heterogeneously exposed to a particular environmental risk, namely the Human-Elephant Conflict (HEC).